Responding to Regulation: The Effects of Changes in Mandatory Retirement Laws on Firm-Provided Incentives - Anders Frederiksen; Colleen Flaherty Manchester (Institute of Labor Economics (IZA), 2019)
The Age Discrimination in Employment Act of 1978 expanded employee age protections to age 70, making the widespread practice by U.S. firms of mandating retirement at age 65 illegal. Building on the work of Lazear (1979), we propose that the law change not only weakened the long-term employment contract, but also contributed to the rise in pay-for-performance incentives. We model the firm's choice between offering long-term incentive contracts with low monitoring requirements and pay-for-performance (PFP) contracts with high monitoring requirements, showing how the law change increased the relative attractiveness of PFP contracts. We test the model's predictions using data from the Baker-Gibbs-Holmstrom firm, evaluating the effect of the law change on the slope of the age-pay profile, turnover rates, and the sensitivity of pay to performance. Further, we find direct evidence of strategic response to the law change by the firm, including the introduction of bonus payments, change in performance management system, and increase in the proportion of top managers. The setting also provides an opportunity to empirically investigate how firms navigate career incentives for employees.
Keywords: M51; M52; 330; incentive pay; pay for performance; long-term incentive contracts; promotions; slot constraints; career incentives